2020
DOI: 10.1126/sciadv.abd3916
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-like proteins that capture and neutralize SARS-CoV-2

Abstract: To combat SARS-CoV-2 and any unknown emerging pathogens in the future, the development of a rapid and effective method to generate high-affinity antibodies or antibody-like proteins is of critical importance. We here report a high-speed in vitro selection of multiple high-affinity antibody-like proteins against various targets including the SARS-CoV-2 spike protein. The sequences of monobodies against the SARS-CoV-2 spike protein were successfully procured within only four days. Furthermore, the obtained monob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(70 citation statements)
references
References 52 publications
1
67
1
1
Order By: Relevance
“…Another example of nanobody library is that it can be constructed from a llama immunized with the recombinant RBD, and this library was selected using a proteomic strategy to achieve anti-RBD nanobodies with picomolar to femtomolar affinity [ 62 ]. Apart from the nanobody, the monobody library can be synthetically constructed and screened against the SARS-CoV-2 S1 subunit, resulting in anti-S1 monobodies with sub-nanomolar to nanomolar affinity [ 63 ]. These monobodies were then applied to capture SARS-CoV-2 particles from the nasal swab samples of patients.…”
Section: Sars-cov-2 Biomarkers and Biorecognition Elementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another example of nanobody library is that it can be constructed from a llama immunized with the recombinant RBD, and this library was selected using a proteomic strategy to achieve anti-RBD nanobodies with picomolar to femtomolar affinity [ 62 ]. Apart from the nanobody, the monobody library can be synthetically constructed and screened against the SARS-CoV-2 S1 subunit, resulting in anti-S1 monobodies with sub-nanomolar to nanomolar affinity [ 63 ]. These monobodies were then applied to capture SARS-CoV-2 particles from the nasal swab samples of patients.…”
Section: Sars-cov-2 Biomarkers and Biorecognition Elementsmentioning
confidence: 99%
“…HRP is horseradish peroxidase enzyme that is used to amplify signal in photometric assays by catalyzing the conversion chemiluminescent substrates. Adapted from [ 63 ], Copyright, The Authors, some rights reserved; exclusive licensee AAAS. Distributed under a Creative Commons Attribution NonCommercial License 4.0 (CC BY-NC) …”
Section: Recent Biosensing Approaches For Detecting Sars-cov-2mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, one study found that none of the 206 RBD-specific monoclonal antibodies derived from single B cells of eight SARS-CoV-2 infected individuals cross-reacted with SARS-CoV or MERS-CoV RBDs (23). Antibody-like monobodies designed to bound to the SARS-CoV-2 S protein also did not bind that of SARS-CoV (24). As a further complicating factor, RNA viruses accumulate mutations over time, which yields antibody resistance and requires the use of antibody cocktails to avoid mutational escape (25).…”
Section: Introductionmentioning
confidence: 99%
“… 24 Antibody-like monobodies designed to bound to the SARS-CoV-2 S protein also did not bind that of SARS-CoV. 25 As a further complicating factor, RNA viruses accumulate mutations over time, which yields antibody resistance and requires the use of antibody cocktails to avoid mutational escape. 26 Not surprisingly, there is now evidence of the emergence of SARS-CoV-2 mutants for which antibodies against the original strain have no or diminished activity.…”
mentioning
confidence: 99%